Jeremy Bentham und Karl Marx: Zwei Perspektiven der Demokratie - Ritschel, Gregor (transcript, 2018)
Despite their differences, Bentham and Marx both fought against anti-democratic interests and ideologies that opposed (and still oppose) universal self-determination for all people.